Analisis Pengaruh Influencer Sosial Media Terhadap Keputusan Masyarakat Indonesia Dalam Pembelian Cryptocurrency - R. Aditya Rayhan Zanesty; Tio Arya Dewa Prakasa; Intania Chantika Alina; Nur Aini Rakhmawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
Cryptocurrency is increasingly showing its popularity as an investment medium that is increasingly taking the attention of the Indonesian people, both common people and experts. This phenomenon is prone to market manipulation by pumping and dumping certain cryptocurrency entities, trapping novice investors.. The respondents of this study were taken from Indonesian people who have cryptocurrencies and social media users. The method used in this study is a descriptive quantitative research method with a total of 151 respondents. The data instrument used in this study was a questionnaire distributed online. The results obtained through surveys that have been conducted prove that social media influencers have a positive and significant influence on Indonesian people's cryptocurrency purchasing decisions.